Implementation of a variable step size NLMS algorithm for speech noise reduction on an ADSP-21065L EZ kit lite board - Go, Allia Donna D.
A clean, noise-free received speech signal is required in many systems, notably in telecommunications systems and automatic speech recognition. To achieve this, a noise reduction system must be applied to the system. An effective adaptive filter algorithm was implemented for the speech noise reduction. This research deals with the implementation of a variable step size Normalized Least Mean Square algorithm for speech noise reduction. The noise reduction system is based on two adaptive line enhancers and a noise estimation filter that reduce both wideband and sinusoidal noise in a noisy speech. A variable step size is used so that the background noise is reduced while high quality of enhanced speech is maintained. The noise reduction system is implemented in hardware, using an ADSP-21065L EZ Kit Lite Board to make the noise reduction process in real time. A working and real-time noise reduction system is the final output of the project. It reduces the background noise and enhances the quality of speech, based on the output signal-to-noise ratio and quality speech. Also, the results of the real-time system concurred with the simulations in MATLAB up to the 4th decimal place. Based on the subjective qualitative testing done, the noise reduction system performs well with speech signal corrupted with sinusoidal noise.